Penegakan Hukum oleh Kepolisian Negara Republik Indonesia Terhadap Tindakan Diskresi - Daseng, Nur Shaleh Muslimin (CV. Social Politic Genius (SIGn), 2023)
This study aims to analyze the extent of discretionary actions carried out by police investigators in law enforcement and the factors that influence it. The type of research used is normative legal research which is descriptive qualitative in nature. Data collection techniques used in this study were interviews and literature study. The data analysis technique used is quantitative data analysis techniques. The results showed that the implementation of discretionary actions by investigators was a series of investigative actions in accordance with Article 18 of Law Number 2 of 2002, and consider the benefits and risks that are really for the public interest. This provision is strengthened in Article 7 section (1) point j of Law Number 8 of 1981. The factors that affect the discretionary act of the Police investigators are the substance of the law factors; legal structure factors; as well as legal culture factors. Political law is expected to be implemented in the development of the legal system starting from the aspects of legal substance, legal structure and legal culture of society.